2007
DOI: 10.1001/archpedi.161.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Fitness Is Negatively Associated With Homocysteine Levels in Female Adolescents

Abstract: Objective: To examine the association between cardiovascular fitness and homocysteine levels in adolescents.Design: Cross-sectional study.Setting: Madrid, Murcia, Granada, Santander, and Zaragoza, Spain.Participants: One hundred fifty-six Spanish adolescents (76 boys and 80 girls) aged (mean ± SD) 14.8 ± 1.4 years.Main Exposures: Cardiovascular fitness was measured by the 20-m shuttle run test. Pubertal stage, birth weight, smoking status, and socioeconomic status were determined, and the sum of 6 skinfold thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
(61 reference statements)
6
30
0
2
Order By: Relevance
“…48,56,57 The levels of C-reactive protein and C3 were inversely associated with cardiorespiratory fitness in prepubertal children, 48 which is consistent with other studies of young people. [58][59][60] Halle et al 59 reported that interleukin-6 levels were as low for obese and fit as for lean and unfit children, while the highest serum interleukin-6 concentrations were found in the obese and unfit group.…”
Section: Physical Fitness and Health Outcomessupporting
confidence: 87%
See 3 more Smart Citations
“…48,56,57 The levels of C-reactive protein and C3 were inversely associated with cardiorespiratory fitness in prepubertal children, 48 which is consistent with other studies of young people. [58][59][60] Halle et al 59 reported that interleukin-6 levels were as low for obese and fit as for lean and unfit children, while the highest serum interleukin-6 concentrations were found in the obese and unfit group.…”
Section: Physical Fitness and Health Outcomessupporting
confidence: 87%
“…61 Studies examining the association between cardiorespiratory fitness and homocysteine levels in young people are scarce. We have found conflicting results in Spanish adolescents 50 and Swedish children and adolescents 62 after controlling for different potential confounders including age, puberty, birth weight, smoking, socioeconomic status, skinfold thickness and methylenetetrahydrofolate reductase 677C4T genotype. Cardiorespiratory fitness was inversely and significantly associated with homocysteine in female Spanish adolescents, 50 whereas no association was found in Swedish children and adolescents.…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 91%
See 2 more Smart Citations
“…But there is also a huge variety in the methodology applied among all the studies, hence, there is difficulty to reach an agreement [5]. Some researchers have demonstrated reduced tHcy concentrations after a training period [12,13]; others have related high PA levels and cardiorespiratory fitness with lower homocysteine concentrations [14,15]. In contrast, some studies have shown higher tHcy concentrations after acute exercise, training period or after a specific sport competition [16][17][18].…”
Section: Introductionmentioning
confidence: 99%